2012
DOI: 10.3390/v4123452
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Molecular Epidemiology and Evolution of Bovine Respiratory Syncytial Virus

Abstract: The bovine respiratory syncytial virus (BRSV) is an enveloped, negative sense, single-stranded RNA virus belonging to the pneumovirus genus within the family Paramyxoviridae. BRSV has been recognized as a major cause of respiratory disease in young calves since the early 1970s. The analysis of BRSV infection was originally hampered by its characteristic lability and poor growth in vitro. However, the advent of numerous immunological and molecular methods has facilitated the study of BRSV enormously. The knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 59 publications
2
41
0
Order By: Relevance
“…The virus consists of a lipid envelope containing three transmembrane surface glycoproteins – G, F and SH. Inside the virion is a helical nucleocapsid composed of a nucleoprotein (N) and a phosphoprotein (P), as well as a viral RNA‐dependent polymerase (L), an M protein and a transcription anti‐termination factor (M2) (Matheise et al., ; Lamb and Parks, ; Sarmiento‐Silva et al., ). Many studies have shown that BRSV exhibits strong homology to the human syncytial virus (hRSV), which is a common cause of acute respiratory disease in infants.…”
Section: Introductionmentioning
confidence: 99%
“…The virus consists of a lipid envelope containing three transmembrane surface glycoproteins – G, F and SH. Inside the virion is a helical nucleocapsid composed of a nucleoprotein (N) and a phosphoprotein (P), as well as a viral RNA‐dependent polymerase (L), an M protein and a transcription anti‐termination factor (M2) (Matheise et al., ; Lamb and Parks, ; Sarmiento‐Silva et al., ). Many studies have shown that BRSV exhibits strong homology to the human syncytial virus (hRSV), which is a common cause of acute respiratory disease in infants.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were in conformity with Mahajan et al, (2013) for IBR. Significant regional differences in the frequency of BRSV have also been reported from studies in Mexico (Sarmiento-Silva et al, 2012).…”
Section: Resultsmentioning
confidence: 75%
“…BRSV has been recognized as an important pathogen responsible of an acute respiratory disease in beef and dairy calves since the early 1970s. 8 The virus has been isolated from cattle in Europe, America and Asia, indicating that BRSV has a worldwide distribution. 9 In China, a total of 600 serum samples obtained from cattle in Heilongjiang province, were tested by indirect ELISA and the positive rate was 27.33%.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 When a proper management practice is implemented, vaccination can be an e®ective tool for preventing and controlling infectious diseases. 4 A commercially available multivalent 5-in-1 vaccine (BR, PI3, BRSV and BVD types I and II) was developed overseas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation